The Adverse Impact of COVID-19 on Islamic Banks in Malaysia - Azam Abdelhakeem Khalid; Hasnah Haron; Norhazlina Ibrahim; Nurazalia Zakaria; Supiah Salleh (Universal Publishers - Boca Raton, Florida, USA, 2024)
Volume 14 Number 3s